A LEGAL SYSTEM APPROACH IN THE HANDLING OF NARCOTIC CRIMES BY CHILDREN - HERYANI, WIWIE; RATNAWATI; MUHAMMAD ASWIN ANAS, ANDI; SUCI WAHYUNI, ANDI (Awang Long Law Review, 2020)
Abuse of narcotics can destroy the joints of community and sustainability of the nation where the target is now leads to the wider community and young generation. The writing of this article uses the statute approach. The results showed the law has given space and special treatment for children in conflict with the law. Including if a child commits a crime in accordance with the provisions of a criminal act in Law Number 35 of 2009 concerning Narcotics. The state comes through regulations to provide special treatment for children who are in conflict with the law to make sure that the children’s rights remain fulfilled. Law enforcement of criminal acts of misuse of narcotics by children in Wajo Regency has been carried out through penal and non-penal efforts. For more effectiveness and humanness of law enforcement, pre-emptive and preventive efforts such as carrying out legal counseling activities for children must be held continuously. This is part of efforts to save children as the nation’s next generation, as mandates in the constitution of the Republic of Indonesia.